Architect's role to improve in-building wireless coverage. Issue 1 (1st January 2020) - Kawser, Mohammad Tanvir; Ahmed, Zebun Nasreen
Abstract: This paper investigates the role of architects in improving in-building wireless coverage, a hitherto unexplored and interdisciplinary domain. While architects are still fully focused on built spaces, in this modern era, the attention of the occupants is gradually being influenced by the virtual surrounds, created by wirelessly connected electronic devices, compared to the quality of actual built spaces, they have around them. The rapid growth of internet usage and related technology is bringing a new demand for building occupation—improved wireless connectivity. This paper presents an in-depth analytical discussion of the challenges of in-building wireless signal coverage. It further elaborates on the additional complexities for support at high frequencies. However, studies show that the nature of the space and its bounding surfaces have a direct influence on signal propagation, and thereby, reception. Therefore, this paper proposes architectural interventions to improve in-building wireless coverage and highlights its necessity. In this process, it proposes a collaboration between radio frequency (RF) engineers and architects, during the design phase of buildings. Considering the scope of architectural design, some guidelines are proposed for the architectural interventions, and the possible outcomes of the interventions are discussed. The improvement in user data rate experience, from one of the proposed architectural solutions, has also been investigated using MATLAB-based simulation, along with necessary derivations. The paper, thus, aims to pave the way for farsighted contributions to in-building wireless coverage, from architects, so that buildings can better cope with the demands of the future.